DNA sequence and structure properties analysis reveals similarities and differences to promoters of stress responsive genes in Arabidopsis thaliana. (2015) - Zhu, Pan; Zhou, Yanhong; Zhang, Libin; Ma, Chuang
Understanding regulatory mechanisms of stress response in plants has important biological and agricultural significances. In this study, we firstly compiled a set of genes responsive to different stresses in Arabidopsis thaliana and then comparatively analysed their promoters at both the DNA sequence and three-dimensional structure levels. Amazingly, the comparison revealed that the profiles of several sequence and structure properties vary distinctly in different regions of promoters. Moreover, the content of nucleotide T and the profile of B-DNA twist are distinct in promoters from different stress groups, suggesting Arabidopsis genes might exploit different regulatory mechanisms in response to various stresses. Finally, we evaluated the performance of two representative promoter predictors including EP3 and PromPred. The evaluation results revealed their strengths and weakness for identifying stress-related promoters, providing valuable guidelines to accelerate the discovery of novel stress-related promoters and genes in plants.